Adherence to integrated care using the ‘Atrial fibrillation Better Care' pathway in asymptomatic patients with atrial fibrillation improves clinical outcomes: A report from the prospective COOL-AF registry - Yodying Kaolawanich; Arjbordin Winijkul; Ahthit Yindeengam; Poom Sairat; Gregory Y.H. Lip; Rungroj Krittayaphong (Heliyon)
Background: Identifying asymptomatic patients with atrial fibrillation (AF) poses a challenge, and their optimal management is less certain, despite similar outcomes to symptomatic AF patients. The ‘Atrial fibrillation Better Care’ (ABC) pathway has been recently proposed as a holistic or integrated care approach for the comprehensive management of symptomatic patients with AF. We aimed to determine the use of the ABC pathway on clinical outcomes in asymptomatic patients with AF. Methods: This is a prospective multicenter registry of patients with non-valvular AF in Thailand conducted between 2014 and 2017. Patients were characterized based on AF-related symptoms at enrollment and their adherence or non-adherence to the ABC pathway. Follow-up data were collected for 3 years to examine the composite endpoint (all-cause death, ischemic stroke/transient ischemic attack [TIA]/systemic embolism [SE], and major bleeding), and the impact of adherence to the ABC pathway. Results: Of a total of 3405 patients included in the study, 785 (23 %) (mean age 69.0 years, 63.7 % male) were asymptomatic at enrollment. Among these asymptomatic patients, 346 (44 %) were adherent to the ABC pathway. Adherence to the ABC pathway was associated with a significantly lower rate of composite endpoints compared to non-adherence (hazard ratio [HR] 0.63, 95 % confidence interval [CI] 0.45–0.90, p = 0.01). Adherence to the ABC pathway was also associated with lower all-cause mortality rates (HR 0.55, 95 % CI 0.35–0.85, p = 0.007). After adjusting for age, gender, and baseline comorbidities, adherence to the ABC pathway remained significantly associated with a lower rate of composite endpoints (HR 0.69, 95 % CI 0.49–0.98, p = 0.03) and all-cause death (HR 0.58, 95 % CI 0.38–0.90, p = 0.01) compared to non-adherence. Subgroup analyses based on sex, age, AF type, risk scores, and comorbidities consistently demonstrated lower hazard ratios for the composite endpoint among patients who were adherent to the ABC pathway. Conclusions: In patients with AF who were asymptomatic, adherence to the ABC pathway was associated with a lower composite endpoint of all-cause death, ischemic stroke/TIA/SE, and major bleeding. This benefit was seen irrespective of sex, age, AF type, risk scores, and comorbidities.